A2 7 Dune Part 1: Charting the Oasis - Scrivener, Callum; Lewis, Dan; Dyer, Thomas (Physics Special Topics, 2024)
We set out to begin determining the feasibility of the fictional planet of Dune being habitable. We conclude that it must orbit its parent star at a distance between 122 and 123.4 AU to have a mean temperature of 560 K, as described by the original book.